MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI SMAN 2 GERUNG - MUHAMMAD ANWAR (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2023)
This study aims to apply the Problem Based Learning (PBL) learning model to improve learning achievement in students at SMAN 2 Gerung for the 2021/2022 academic year. The design of this research is classroom action research which takes place in two cycles. The subjects of this study were 56 class XII students. Data collection was carried out using the test method to obtain data on students' learning achievement in permutation material given at the end of each cycle and observation to obtain learning activity data. The collected data were analyzed by descriptive qualitative. The research results obtained were the increase in students' learning achievements as evidenced by the results of learning aspects of the original knowledge in the initial conditions of 42.85% of students who were able to analyze concepts from Permutations. The average cognitive score of students in cycle I was between 54-61. After the arithmetic test using the Group Achievement Index, the GPA was obtained at 69.53% and after the second cycle the cognitive average values of the students changed between 62-69 then the arithmetic test was carried out and the GPA was obtained at 76.38%, so the interpretation of group achievement was included in HIGH criteria. Thus, from the results of the arithmetic test using the GPA, it can be seen that the difference in group achievement scores between cycle I and cycle II for all class XII students in semester 2 is 6.85%. ABSTRAKPenelitian ini bertujuan menerapkan model pembelajaran Problem Based Learning (PBL)  untuk meningkatkan Prestasi belajar pada peserta didik di SMAN 2 Gerung tahun pelajaran 2021/2022. Desain penelitian ini adalah penelitian tindakan kelas yang berlangsung dalam dua siklus. Subyek penelitian ini adalah peserta didik kelas XII yang berjumlah 56 orang. Pengumpulan data dilakukan dengan metode tes untuk memperoleh data Prestasi Belajar peserta didik Pada Materi Permutasi  yang diberikan pada setiap akhir siklus dan  observasi untuk memperoleh data aktivitas belajar. Data yang terkumpul dianalisis secara deskriptif kualitatif. Hasil penelitian yang diperoleh adalah meningkatnya Perestasi Belajar peserta didik yang dibuktikan dengan hasil belajar aspek pengetahuan semula pada kondisi awal 42,85% siswa yang mampu menganalisis konsep dari Permutasi . Nilai rata-rata kognitif siswa pada siklus I antara 54-61. Setelah dilakukan uji hitung dengan menggunakan Indeks Prestasi Kelompok didapatkan IPK sebesar 69,53% dan Setelah dilakukannya siklus II nilai rata-rata kognitif siswa mengalami perubahan antara 62-69 kemudian dilakukan uji hitung didapatkan IPK sebesar 76,38% maka penafsiran presatsi kelompok termasuk dalam kriteria TINGGI. Dengan demikian dari hasil uji hitung menggunakan IPK terlihat perbedaan nilai prestasi kelompok anatara siklus I dan siklus II pada seluruh siswa kelas XII semester 2 sebesar 6,85%.